2016
DOI: 10.20409/berj.2016321805
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Financial Literacy on the Behavioral Biases of Individual Stock Investors: Evidence from Borsa Istanbul

Abstract: Financial literacy and behavioral biases are critical factors affecting the financial decisions and behaviors of investors. We survey 596 individual stock investors to measure their financial literacy, to examine their behavioral biases and to investigate the relationship between financial literacy and behavioral biases. Results suggest that around half of the investors have a low financial literacy level, their main source of financial information is advice from parents or friends, and they have a high level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 16 publications
1
30
0
9
Order By: Relevance
“…Duong et al (2015) found that investor's knowledge and their decisions about investment and savings can be enhanced at their age of retirement and it seems that demographic factors like gender, age, income are associated with the behaviour of the investor. Ateşa et al (2016) describes a substantial association amongst behavioural biases variables and the level of financial literacy. The finding stated that financial literacy shows a negative effect on framing, overconfidence and loss aversion.…”
Section: Financial Literacy and Investment Decisionmentioning
confidence: 99%
“…Duong et al (2015) found that investor's knowledge and their decisions about investment and savings can be enhanced at their age of retirement and it seems that demographic factors like gender, age, income are associated with the behaviour of the investor. Ateşa et al (2016) describes a substantial association amongst behavioural biases variables and the level of financial literacy. The finding stated that financial literacy shows a negative effect on framing, overconfidence and loss aversion.…”
Section: Financial Literacy and Investment Decisionmentioning
confidence: 99%
“…Mouna and Anis (2016) found that people with low financial literacy are less likely and hesitant to invest in the stock market and men are more financially literate than women. Ateş et al, (2016) found that half of the investors lack in financial literacy (parents or friends happen to be their main source of information) and they encounter the behavioural biases at a high level. The biases like over-optimism, representativeness and confirmation have a positive relationship with financial literacy and the biases like loss aversion, overconfidence, framing and cognitive dissonance have a negative relationship with financial literacy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, there is a significant difference in financial literacy among UAE investors across gender, work activity, and education level [29], [30] showed that age and education are positively related with financial literacy and financial well-being. Moreover, men as well as those who are married tend to be more financially literate [30], [31] provided supporting evidence from Borsa Instanbul that female, married, and retirement-age investors exhibit higher level of financial literacy than male, single and working-age investors. [32], [33] confirmed age to be a significant determinant of financial literacy.…”
Section: Are Vietnamese Individual Investors Financially Literate? a mentioning
confidence: 81%